Implementation of The Justice Restoration System Towards Labor Crimes in the Framework of Labor Law Enforcement - Aminy, Risya Ainun Zakiyah; Karsona, Agus Mulya; Singadimedja, Holyness (Law Development Journal, 2024)
This research is motivated by the need for the application of restorative justice in resolving cases of labor crimes in Indonesia. This approach is considered a more effective alternative in achieving justice that prioritizes recovery and dialogue between perpetrators, victims, and the community concerned. Currently, many cases of labor violations such as below-standard wages, unilateral termination of employment, and violations of basic workers' rights have not been resolved properly through the formal justice system. Therefore, restorative justice is expected to provide a more inclusive and humane solution compared to the retributive approach which only focuses on punishment. This study uses a normative legal method with a literature study approach and descriptive qualitative data analysis. The normative legal method involves an analysis of existing legal principles, theories, and rules. Primary legal materials used include laws and regulations such as the Employment Law and regulations related to restorative justice. Secondary legal materials include scientific literature, articles, and journals related to the topic being studied. While tertiary legal materials consist of legal dictionaries and encyclopedias that support the understanding of the legal concepts discussed. Data collection from various literature, books, journals, and legal documents related to restorative justice and employment law. The results of the study indicate that the application of restorative justice in employment cases can provide a more humane and equitable solution, by prioritizing the restoration of losses experienced by victims and the restoration of social relations in the workplace. However, there are a number of obstacles in its implementation, such as the lack of understanding of law enforcers and limited regulations that support this approach. Based on these findings, this study suggests strengthening the capacity of law enforcers and the preparation of clearer regulations to encourage the optimization of the application of restorative justice in resolving employment crimes. This study is expected to contribute to the development of a more inclusive and responsive law enforcement concept to the needs of the working community in Indonesia.